Engaging nursing students in a COVID‐19 Point‐of‐Care rapid screening clinic. Issue 5 (10th June 2022) - Dhari, Ranjit; Haase, Kristen; Ranger, Manon; Tan, Elsie; Affleck, Frances; Bailey, Elisabeth; Wong, Sabrina T.
Abstract: Background: The COVID‐19 pandemic has globally impacted nursing education, particularly clinical learning opportunities for undergraduate nursing students. Purpose: In this paper, we report on an educational activity wherein students participated in a COVID‐19 Rapid Antigen Testing (RAT) clinic on a Canadian university campus. Methods: Between February–April 2021, in the second term of a five‐term accelerated program, nursing students ( n  = 60) participated in a nurse‐led COVID‐19 RAT clinic for students and staff living or working in congregate housing. Students participated in education activities which exposed nursing students to the full range of community health nursing roles in a pandemic. Results: From clinical, research, policy, and public health, this educational activity acted as a microcosm of the critical roles that nurses employ in the health ecosystem. Conclusion: We offer lessons learned about implementing this activity, and how these lessons can be applied to routine and exceptional nursing curriculum.